Analysis The Potential of Building Information Modeling (BIM) and Lean Construction in Reducing Construction Waste through Modeling: A Case Study of SMP Negeri 6 Surakarta - Batee, Arvin Rabbani; Amar, Tsulis Iqbal Khairul; Priyanto, Budi (Prosiding Seminar Nasional Teknik Sipil UMS, 2025)
The construction industry has a significant contribution to the generation of construction waste which has the potential to increase costs and cause environment impacts if not managed optimally. This study aims to analyze the effect of the application of Building Information Modeling (BIM) and Lean Construction principles in reducing construction waste in the construction project of SMP Negeri 6 Surakarta. The methods used in this research include the utilization of BIM for waste estimation and calculation and the Delphi method to identify the main factors causing waste generation. The results showed that BIM-based planning using Autodesk Revit contributed positively to the reduction of construction waste, with a decrease in the percentage of reinforcement steel waste by 4.83% and concrete waste by 8.55%. The main factors contributing to waste generation include initial design that does not consider aspects of material efficiency, material waste due to overuse, inefficiency in the implementation process, repetition of work, and lack of control over ready mix concrete and site mix. In addition, material damage at the procurement stage is also one of the significant causes of construction waste generation. These findings indicate that the application of BIM and Lean Construction can be an effective strategy for reducing construction waste and improving resource efficiency in development projects.